Effects of segmented thermal-vibration stress relief process on residual stresses, mechanical properties and microstructures of large 2219 Al alloy rings - Song, Hechuan; Gao, Hanjun; Wu, Qiong; Zhang, Yidu (Journal of alloys and compounds, 2021)
•A STVSR process was proposed to stress relief for large 2219 Al-Cu alloy transition rings.•The residual stresses decreased and mechanical properties improved after STVSR.•The underlying mechanisms of residual stress relief by STVSR were quantitatively revealed.•The residual stress relief is attributed to the dynamic evolution of dislocations and precipitated phases.•The improvement of mechanical properties mainly depends on the precipitated phases and is also affected by residual stresses. Large 2219 Al-Cu alloy transition rings are extensively employed in propellant tanks of heavy launch vehicles. These rings have a diameter exceeding 5 m or even reaching 10 m, with a less than 2% thickness-to-radius ratio, and low stiffness which can cause machining deformation due to the residual stress. Thus, residual stress relief of these rings is necessary in their extreme manufacture. A novel effective method is thermal-vibration stress relief (TVSR), which integrates the conventional thermal stress relief (TSR) and vibratory stress relief (VSR); however, the existing TVSR equipment cannot meet the requirements of large rings, and the underlying mechanisms of TVSR remain unclear and a quantitative interpretation is still lacking. Therefore, a segmented TVSR (STVSR) process suitable for large rings was proposed and the corresponding experiment was carried out with a self-made STVSR experiment platform. Then this study investigated the evolution and distribution laws of the residual stresses, tensile properties, Vickers hardness, dislocations, precipitated phases and metallography during STVSR. Based on the experimental results, multi-scale mechanics theory and strengthening mechanisms were applied to quantitatively reveal the underlying mechanisms of residual stress relief by STVSR. The results showed that the circumferential and axial residual stress relief rates can reach 44.43% and 45.14% after STVSR, respectively. The residual stress relief after STVSR is attributed to the dynamic evolution of dislocations and precipitated phases in the material. The improvement of mechanical properties mainly depends on the precipitated phases and is also affected by the residual stress. The findings confirm the significant effects of STVSR on metal plasticity and provide valuable insight into the underlying mechanisms of TVSR.